Design and implementation of WiFi device signature scanner / Ahmad Uzaimi Jaafar - Jaafar, Ahmad Uzaimi (Faculty of Information Technology and Quantitative Sciences, 2005)
With the mass deployment of wireless network (WiFi) in the world today, the usefulness of WiFi network are not only limited to connect attached host together or connect it to the internet. With the absence of wire WiFi network can be use to create a location base system to detect device or host in its network. This is what we trying to achive in this thesis. By creating an access point that can scan the entire device in the network and provide some sort of device identification we can provide a location based service in a wireless network. From this project, it will hopefully allow new application to be developed based on this system to further exploit the features available on a wireless network.